2013
DOI: 10.1002/asjc.760
|View full text |Cite
|
Sign up to set email alerts
|

Design of Fixed Structure Pid Controller for Nonlinear System with Saturation

Abstract: An approach is presented to design a PID controller for a given plant with saturation. Based on the describing function models of saturation and the method of determining the sets of stabilizing a PID controller for a linear plant with time delay or one that is delay free, the new equivalent inverse Nyquist plots are given for different sinusoidal input amplitudes of saturation. The PID controller parameters are selected from intersecting sets of stabilizing PID parameter regions for different input amplitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…A detailed review of models and the methods used in the modern theory of optimal control can be found in works [8,9]. Works [10][11][12][13][14][15][16][17][18][19][20] contain references to a large number of studies of theoretical and applied characters which are devoted to problems of optimal control. The linear-quadratic (LQ) problem of optimal control by dynamic systems with convex functional and constraints on values of control is investigated in [13].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review of models and the methods used in the modern theory of optimal control can be found in works [8,9]. Works [10][11][12][13][14][15][16][17][18][19][20] contain references to a large number of studies of theoretical and applied characters which are devoted to problems of optimal control. The linear-quadratic (LQ) problem of optimal control by dynamic systems with convex functional and constraints on values of control is investigated in [13].…”
Section: Introductionmentioning
confidence: 99%